Prevalence of low back pain, back pain beliefs and quality of life among undergraduate students in IIUM Kuantan - Che Hasan, Muhammad Kamil; Asram, Nurul Asyiqin; Nik Mohd Hatta, Nik Noor Kaussar; Jamaludin, Thandar Soe Sumaiyah; Sidek Ahmad, Zulkhairul Naim (2021)
Objective: Studies reported a high prevalence of low back pain among healthcare-related staff. However, the association between undergraduate students, who are potentially exposed to the same occupational risks has never been demonstrated. Thus, a cross-sectional study was conducted to determine the prevalence of low back pain, back pain beliefs and quality of life among the undergraduate students in International Islamic University Malaysia, Kuantan, Pahang. Methodology: Undergraduate students who studying in academic session 2020/2021 and literate in English were recruited to participate in this study using the convenience sampling method. A standardized Nordic Musculoskeletal Questionnaire was used to assess low back pain status among the respondents. Back pain beliefs and quality of life were assessed by using the Back Beliefs Questionnaire (BBQ) and 12-items Short Form Health Survey (SF-12) respectively. Results: A total of 618 undergraduate students participated in this study with 78.3% reported having low back pain in their entire lifetime, and 33.2% for the past 7 days. Female was found to have higher reported low back pain as compared to male (X2=10.899, df=1, p=0.001). The majority of students had negative back pain beliefs especially in those who experienced low back pain (X2= 8.062, df= 1, p= 0.005). Meanwhile, pharmacy students reported with highest negative back pain beliefs with a significant p-value (p=0.003). However, the reported low back pain does not impact their mental (p=0.747), physical (p=0.156), and quality of life (p=0.051). Conclusion: This study has shown a high prevalence among undergraduate students taking Medicine, Nursing, Dentistry and Pharmacy. The Pharmacy students had higher negative back pain beliefs as compared to others. The low back pain does not affect their mental, physical and quality of life.